The Effectiveness of the Integrative IBL Learning Model and Visual Media in Enhancing Conceptual Understanding of Balaghah: A Quasi-Experimental Study on Ulya Grade Students - Rita Puspitasari; Muhammad Alaika Nasrulloh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Balaghah learning is often considered difficult and inapplicable by students due to the textual-conventional approach that is far from their context. This research offers significant novelty thru the development of an integrative learning model that combines the Inquiry-Based Learning (IBL) framework with specialized visual media to create contextual and meaningful balaghah learning experiences. This research aims to test the effectiveness of an inquiry-based balaghah learning model integrated with visual media in enhancing students' conceptual understanding. The novelty of this research lies in the integration of the inquiry process and visual rhetoric analysis, which has not been widely developed in balaghah teaching. The research uses a quasi-experimental design with a control group and an experimental group. The research participants were 40 students from the ulya class (equivalent to Madrasah Aliyah) of Pondok Pesantren Mukhtar Syafa'at, divided into two groups of 20 students each. The experimental group was given inquiry-based balaghah learning with the aid of visual media, while the control group followed conventional text-based learning. The research results show that the experimental group achieved higher conceptual understanding scores compared to the control group. The increase is consistent with an effect size in the medium to large category, indicating a practically significant impact. Furthermore, students in the experimental group were able to identify, differentiate, and analyze rhetorical elements in a visual context, while the control group tended to be limited to rote memorization. The conclusion of this research is that inquiry-based balaghah learning with visual media is proven to be more effective compared to conventional methods. These findings contribute to the development of a more contextual and student-centered pedagogy of balaghah.